Personal Protective Equipment and Infection Control: Evaluating the Impact on Healthcare Worker Safety – A Review - aloufi, Raied Aied; Aljohani , Mousa Abdulbaki Marzoq; AL- Harbi, Myaad Ateeq Mohammad Ali; alharbi , Hadeel saleh zaid; Alharbi, Abdulaziz Shabbab Olayethah; Najdi , Ibrahim Mousa Mohammed; Al Sharif, Rahma Nasser Bayan; Aljohani , Fahad Abdullah Eid; AlHarbi, Naif Ali Abdullah; Alharbi , Hamdi Rshdan (Journal of Ecohumanism, 2024)
Personal protective equipment (PPE) is a cornerstone of infection control, serving as a critical barrier between healthcare workers (HCWs) and infectious agents. This review evaluates the effectiveness of PPE in reducing healthcare-associated infections (HAIs) and safeguarding HCWs, with a focus on its role during recent global outbreaks such as COVID-19. A systematic search of peer-reviewed studies from 2016 onward revealed that proper PPE use significantly reduces infection risks, with reductions of up to 85% reported during high-risk scenarios. However, challenges such as resource shortages, improper usage, discomfort, and compliance issues persist, particularly in low- and middle-income countries (LMICs). The review highlights disparities in PPE availability and effectiveness between high-income countries (HICs) and LMICs, underscoring the need for equitable access and targeted interventions. Recommendations include enhancing supply chains, providing regular training, and promoting innovation in PPE design to improve usability and compliance. These findings underscore the essential role of PPE in infection prevention and the importance of sustained efforts to address existing barriers and ensure HCW safety globally.